Evaluating the Impact of Oil Refinery on Landscape Values Perception and Mental Health: A Case Study of Tehran - Mahdi Gheitasi; David Serrano Giné; Yolanda Pérez Albert (Land)
In today’s society, stress is recognized as a major contributor to illness. It can be reduced through exercise, which lowers stress hormones, and exposure to daylight, which regulates hormones such as cortisol and melatonin. Furthermore, the design and perception of the environment can indicate danger or safety, influencing stress levels and mental health. This study examines the Tehran Oil Refinery’s impact on local residents’ perceptions of landscape values and mental health. Oil refineries, which use compounds derived from natural gas or crude oil, pose both short- and long-term environmental and health risks. Using a Geographic Information System for Public Participation (PPGIS), the study investigates how the industrial landscape surrounding the Tehran Oil Refinery influences residents’ emotional responses and stress levels. The study collects sociodemographic data, self-perceived health data, and landscape valuations before and after photography interventions. The findings indicate a complex relationship between the refinery’s presence and perceptions of landscape values. Manipulated photographs used in the study show how visual elements can influence emotional responses, highlighting a direct link between stress and environmental perception. This case study adds to larger discussions about the effects of industrialization on public mental health and the environment, emphasizing the importance of incorporating public perception into urban planning in order to achieve sustainable development.